2006
DOI: 10.1007/s10749-006-0016-6
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the corrosion resistance of equipment due to the use of film-forming amines

Abstract: Results of a study of tube specimens cut from hot-water boilers show that film-forming octadecyl amine (ODA) used in the process of preservation removes deposition from the surface of the metal. An ODA film is preserved on the surface after repeated washing of the latter with hot water. The concentration of chlorides at the surface of the metal after treatment with ODA is lower than before the treatment.It is known that in the case of long-term standstill (over 7 days) of the power equipment of a cogeneration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…where n is an integer between 0 and 7, R1 is an unbranched aliphatic chain (such as alkyl or alkenyl) with 12-22 carbon atoms, and R2 is a short aliphatic chain (such as alkyl or alkenyl group) that usually contains 1-4 carbon atoms. The simplest FFA is ODA, n = 0, R1 = C 18 H 37 , which is also the most widespread in the energy sector 4,15,[28][29][30][31][32] and has the longest history of utilization. It belongs to the primary aliphatic amines with a saturated carbon chain.…”
Section: Physical and Chemical Properties Of Ffamentioning
confidence: 99%
See 1 more Smart Citation
“…where n is an integer between 0 and 7, R1 is an unbranched aliphatic chain (such as alkyl or alkenyl) with 12-22 carbon atoms, and R2 is a short aliphatic chain (such as alkyl or alkenyl group) that usually contains 1-4 carbon atoms. The simplest FFA is ODA, n = 0, R1 = C 18 H 37 , which is also the most widespread in the energy sector 4,15,[28][29][30][31][32] and has the longest history of utilization. It belongs to the primary aliphatic amines with a saturated carbon chain.…”
Section: Physical and Chemical Properties Of Ffamentioning
confidence: 99%
“…The simplest FFA is ODA, n = 0, R1 = C 18 H 37 , which is also the most widespread in the energy sector 4,15,28–32 and has the longest history of utilization. It belongs to the primary aliphatic amines with a saturated carbon chain.…”
Section: Physical and Chemical Properties Of Ffamentioning
confidence: 99%
“…Presently, in the thermal power industry, the utilization of FAPs into implementing medium- and long-term boiler maintenance after shutdown has become one of the main maintenance methods [ 1 , 2 ]. The operating experiences of many thermal power plants showed that the shutdown protection of FAPs can effectively reduce the corrosion rate during the shutdown period.…”
Section: Introductionmentioning
confidence: 99%
“…Chernyshev et al 16 studied the standby corrosion prevention by ODA in a cogeneration plant. By analyzing eight hot water boiler stations, Chernyshev et al showed that an ODA layer preserved most surfaces after a long-term outage.…”
Section: ■ Introductionmentioning
confidence: 99%